ANXA7 Regulates Platelet Lipid Metabolism and Ca2+ Release in Arterial Thrombosis. Issue 4 (28th June 2021) - Manke, Mailin-Christin; Geue, Sascha; Coman, Cristina; Peng, Bing; Kollotzek, Ferdinand; Münzer, Patrick; Walker, Britta; Huber, Stephan M.; Rath, Dominik; Sickmann, Albert; Stegner, David; Duerschmied, Daniel; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Platelet activation after contact to subendothelial collagen leads to acute arterial thrombosis. ANXA7 (Annexin A7) is a phospholipid-binding protein participating in the regulation of intracellular Ca 2+ and exocytosis. Objective: The present study aimed to determine the role of ANXA7 in platelet Ca 2+ signaling and lipid metabolism during platelet activation in arterial thrombosis using the ANXA7 inhibitor 6-amino-2, 3-dihydro-3-hydroxymethyl-1, 4-benzoxazine (ABO) and gene-targeted mice lacking Anxa7 ( Anxa7 −/− ). Methods and Results: ANXA7 is strongly expressed in platelets. Functionally, luminescence aggregometry revealed significantly abrogated aggregation and secretion of ABO-treated or Anxa7 −/− platelets when compared with untreated or Anxa7 +/+ platelets after activation with collagen or the GPVI (glycoprotein VI)-specific agonist collagen-related peptide. Furthermore, while both thrombus formation on collagen-coated surfaces under high arterial shear rates in ABO-treated or Anxa7 -deficient whole blood, and thrombotic vascular occlusion after FeCl3 -induced injury in vivo in Anxa7 −/− bone marrow chimeric mice were significantly diminished, no prolongation of bleeding time was observed in ABO-treated or Anxa7 −/− mice. Fura-2-AM spectrofluorimetry unraveled a blunted [Ca 2+ ]i increase in ABO-treated or Anxa7 −/− platelets after GPVI stimulation. Due to an abolished phospholipase Cγ2 phosphorylation, Anxa7 −/− platelets displayed abrogated intracellular Ca 2+ mobilization following collagen-related peptide-dependent platelet activation. Quantitative lipidomics analysis further revealed that ANXA7 critically affects platelet oxylipin metabolism following GPVI-dependent platelet activation. Anxa7 −/− platelets showed a significantly reduced generation of several bioactive metabolites, particularly thromboxane A2 and 12(S)-hydroxy-eicosatetraenoic acid. Finally, defective phospholipase Cγ2 phosphorylation and blunted [Ca 2+ ]i increase in Anxa7 −/− platelets could be rescued by exogenous addition of 12(S)-hydroxy-eicosatetraenoic acid, indicating that ANXA7 is a critical regulator of the platelet 12-lipoxygenase in GPVI-dependent platelet Ca 2+ signaling during arterial thrombosis. Conclusions: The present study unravels ANXA7 as a regulator of oxylipin metabolism and Ca 2+ -dependent platelet activation downstream of GPVI. ANXA7 plays an important role in platelet signaling during arterial thrombosis and thus may reflect a promising target for novel antiplatelet strategies.